Metabolite itaconate in host immunoregulation and defense - Wenchang Yang; Yaxin Wang; Kaixiong Tao; Ruidong Li (Cellular & Molecular Biology Letters, 2023)
Abstract Metabolic states greatly influence functioning and differentiation of immune cells. Regulating the metabolism of immune cells can effectively modulate the host immune response. Itaconate, an intermediate metabolite derived from the tricarboxylic acid (TCA) cycle of immune cells, is produced through the decarboxylation of cis-aconitate by cis-aconitate decarboxylase in the mitochondria. The gene encoding cis-aconitate decarboxylase is known as immune response gene 1 (IRG1). In response to external proinflammatory stimulation, macrophages exhibit high IRG1 expression. IRG1/itaconate inhibits succinate dehydrogenase activity, thus influencing the metabolic status of macrophages. Therefore, itaconate serves as a link between macrophage metabolism, oxidative stress, and immune response, ultimately regulating macrophage function. Studies have demonstrated that itaconate acts on various signaling pathways, including Keap1-nuclear factor E2-related factor 2-ARE pathways, ATF3–IκBζ axis, and the stimulator of interferon genes (STING) pathway to exert antiinflammatory and antioxidant effects. Furthermore, several studies have reported that itaconate affects cancer occurrence and development through diverse signaling pathways. In this paper, we provide a comprehensive review of the role IRG1/itaconate and its derivatives in the regulation of macrophage metabolism and functions. By furthering our understanding of itaconate, we intend to shed light on its potential for treating inflammatory diseases and offer new insights in this field.